Development of Learning Media Assisted by Baamboozle in Pancasila Education for Third Grade Elementary School Students - Layliyatul Iswinda Mufarohatin; Novialita Angga Wiratama; Ina Agustin (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This research is based on the sub-optimal utilization of diverse learning media in Pancasila Education subjects in Elementary Schools, which impacts student motivation and learning outcomes. This research is directed at designing and developing new learning media by integrating the Baamboozle platform in Pancasila Education learning for third-grade elementary school students and testing the extent of the feasibility, ease of use, and success of the product when applied in learning. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects consisted of three validators, namely media experts, material experts, and language experts, as well as limited trials on 24 third-grade B students of UPT SDN Semanding and homeroom teachers as practical respondents. The data collection process in this study used several instruments including direct observation, structured interviews, and assessment sheets from experts. Researchers also collected responses from teachers and students using questionnaires, while improvements in learning outcomes were measured through a pretest and posttest scheme. Research data confirms that the Baamboozle-based learning instrument obtained validation from media experts of 98.46%, material experts of 95.55%, and language experts of 97.78% with a very valid category. The results of the teacher and student response questionnaires each obtained a percentage of 100% with a very practical category. In addition, student learning outcomes increased from an average pretest of 50.91 to a posttest of 88.5, with an N-Gain value of 0.76 which is included in the high category. Based on these results, the Baamboozle-assisted learning media is proven to be feasible, easy to implement, and improves the quality of learning used in Pancasila Education learning for third-grade elementary school students.